Pengaruh Sales Promotion, Content Marketing, Dan Shopping Lifestyle Content Creator Tiktok Terhadap Keputusan Impulse Buying Pada E-Commerce Shopee - Bagas Mahendra Indriawan; Ignatius Hari Santoso (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study is to know effect of Sales Promotion, Content Marketing and Shopping Lifestyle content creator TikTok on Impulse Buying. Population in this study are students in the city of Semarang who have shopped at e-commerce Shopee and also have social media Tiktok then sample used in the study was 100 respondents who were taken by purposive sampling. In collecting data in this study using a questionnaire through Google Form, while secondary data using literature study. The tool used in this research is PLS. Based on the test results of the Sales Promotion (X1) variable on Impulse Buying (Y) there is a positive and significant effect with the magnitude of the effect being 0.250. The results of testing the effect of the variable Content Marketing (X2) with Impulse Buying (Y) is that there is a positive and significant effect with the magnitude of the effect is 0.390. The results of testing the effect of the Shopping Lifestyle (X3) variable with Impulse Buying (Y) is that there is a positive and significant effect with the magnitude of the effect being 0.324